Noise Citra dan Estimasi Dosis Radiasi dengan Aktifasi Sistem Automatic Exposure Control pada Pemeriksaan Computed Tomography Kepala - Rini Indrati; Azlan Yazid; Bagus Abimanyu (Jurnal Imejing Diagnostik (JImeD), 2015)
Background: Of the ways to maintain optimum image quality and reduce the intensity of radiation to patients is optimizing the value of tube current (mAs) using parameter of Automatic Exposure Control (AEC) or mA modulation. But at the fact in hospital, protocol parameter Automatic Exposure Control (AEC) is not activated or OFF on head computed tomography examination.Methods: This study was a quatitative experimental study. Subject of this study was head phantom. Phantom scanned with four treatments, the activation parameters was sure exp.3D-high quality, sure exp.3D-standard, sure exp.3D-low dose and AEC-OFF. Noise was analyzed using the standard deviation of the CT Number. The ROI of approximately 5 mm2 the intracranial area which is divided into three quadrants namely the anterior region, central region and posterior region of neck which is uniform are aof phantom.Results: The results showed significant differences when parameter automatic exposure control was activated and disabled or AEC-OFF with p value was 0.003 (0,05). Furthermore, based on the scanning results in a change of  radiation dose estimation to the highest doses value of the activation parameters of automatic exposure control and the lowest dose when parameter automatic exposure control deactivated or AEC-OFF.Conclusion: Activation parameters of automatic exposure control (sure exp. 3D) on a head CT examination image noise tends to decline and give a higher radiation dose than when parameter automatic exposure control deactivated or AEC-OFF.